Distribution of BCMV strains in Kashmir valley and identification of resistant sources of Phaseolus vulgaris - Hamid, Aflaq; Ahmad, Mushtaq; Padder, B.A.; Shah, M.D.; Sofi, T.A.; Mohaddin, F.A. (The Indian Journal of Genetics and Plant Breeding, 2016)
Extensive survey of 100 commercial bean growing areas of Kashmir was conducted during kharif 2009 and 2010 indicated only 13 locations to be free from Bean Common Mosaic Virus (BCMV) disease. The disease incidence ranged from 0.50 to 85%. The maximum disease incidence was recorded in Srinagar followed by districts Anantnag and Bandipora, respectively. Confirmation of the association of BCMV with each isolate was made by mechanical transmission, DAC-ELISA and RT-PCR. Evaluation of eighty-five accessions of common bean of diverse origin under controlled glass-house conditions identified R-40, R-155, R-3, B-6, Pencil white, SKAU-B-02, SKAU-B-01, Pointed lady, TO, P1207262, TU, KRC-5, R-14, Jubila, Contender and Monroe accessions to be resistance against all the five strains (NL-1, NL-1n, NL-7, NL-7n and NL-4) of BCMV prevalent in Kashmir.